Surface Modification of Solution-Processed ZrO2 Films through Double Coating for Pentacene Thin-Film Transistors - Kwon, Jin-Hyuk; Bae, Jin-Hyuk; Lee, Hyeonju; Park, Jaehoon (Journal of the Korean Physical Society, 2018)
We report the modification of surface properties of solution-processed zirconium oxide (ZrO 2 ) dielectric films achieved by using double-coating process. It is proven that the surface properties of the ZrO 2 film are modified through the double-coating process; the surface roughness decreases and the surface energy increases. The present surface modification of the ZrO 2 film contributes to an increase in grain size of the pentacene film, thereby increasing the field-effect mobility and decreasing the threshold voltage of the pentacene thin-film transistors (TFTs) having the ZrO 2 gate dielectric. Herein, the molecular orientation of pentacene film is also studied based on the results of contact angle and X-ray diffraction measurements. Pentacene molecules on the double-coated ZrO 2 film are found to be more tilted than those on the single-coated ZrO 2 film, which is attributed to the surface modification of the ZrO 2 film. However, no significant differences are observed in insulating properties between the single-and the double-coated ZrO 2 dielectric films. Consequently, the characteristic improvements of the pentacene TFTs with the double-coated ZrO 2 gate dielectric film can be understood through the increase in pentacene grain size and the reduction in grain boundary density.